Tracing the depth-dependent changes in organic carbon and nutrient fluxes using high-resolution 228Ra profiles in the upper East Sea (Japan Sea) - Cho, Hyung-Mi; Han, Yongjin; Kim, Young-Il; Baek, Cheolmin; Kim, Guebuem (Frontiers in Marine Science, 2022)
Vertical profiles of 228Ra (half-life: 5.75 years) in the ocean provide valuable information on water mixing and ages of the upper ocean. However, its application is hampered by extremely low levels of 228Ra in the deep ocean. In this study, we measured high-resolution 228Ra/226Ra ratio profiles (>21 depths) in the East Sea (Japan Sea) by mooring Mn-fiber. Using the measured 228Ra profile from 228Ra/226Ra ratios and 226Ra activities, together with other previously published data, we estimated the vertical eddy diffusivity (8.7–9.6 cm2 s-1) in the permanent thermocline and water ages (10–15 years) in the upper 500–1000 m range. The estimated decomposition rate of organic carbon based on oxygen utilization rates using Ra-ages between 100 and 1000 m was 4.4 ± 0.8 mol C m-2 yr-1. Our results show that 50% of the upward nutrients through 100 m support export production, and that dissolved organic carbon accounts for 20% of carbon export. This 228Ra approach provides a holistic understanding of carbon and nutrient cycles in the ocean.